Effect of some oil cakes and saw dust application on root-knot (Meloidogyne incognita) infection and root nodulation of soybean - PRAMILA GUPTA, S.M. MISHRA * and (Indian Phytopathology, 2002)
In pot experiments, the application of sawdust or oil cakes of mustard, Azadirachta indica, Linum usitatissimum, Madhuca longifolia or Ricinus communis increased growth of soyabean and reduced nematode damage.